Manajemen Sarana Dan Prasarana Pendidikan Untuk Meningkatkan Mutu Pembelajaran Di Sekolah - Sari Nusantara Putri (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to describe the management of educational facilities and infrastructure to improve the quality of learning at Pamekasan 6 State Junior High School. The research method is qualitative through a case study approach. Data collection techniques: interviews, observation, and documentation. Data processing techniques: reduction, data presentation, and conclusion. Wetness engineering data: credibility and confirmability. The research results show: (1) planning: collecting analysis of facility and infrastructure needs. (2). Procurement: purchasing items that prioritize learning needs. (3) inventory: recording goods in the inventory book. (4) maintenance: cleaning classroom facilities and building maintenance. (5) removal: throwing away items that are unfit and do not meet the criteria.